Implementasi Gamifikasi dengan Animasi Lottie pada Aplikasi Media Belajar IPA SMPN 1 Sumberrejo - Muhammad Farhan Abdur Rosyid; Lutfi Fanani; Tri Afirianto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
SMPN 1 Sumberrejo is one of the schools that implements online learning. The learning media platform currently used is considered less effective in supporting the learning process of students which has an impact on decreasing student interest in learning. The development of learning applications with the implementation of gamification and Lottie animation can help the learning process with the online method applied to groups of students at SMPN 1 Sumberrejo. This research was carried out by adopting the Rapid Application Development (RAD) development method. Concepts and needs analysis resulted from the need discovery process that involved students directly. The system design is obtained through the interpretation of the needs analysis which is carried out repeatedly to get the concept that is in accordance with what the user wants. The implementation of the design on the learning application is carried out in 2 parts, namely the user design stage which allows changes to occur and the finalization stage to optimize the algorithm and write code. The first test is black box testing to ensure that the functional system runs according to the design, which results in 100%. The second test is a safety-runtime test which proves that the application does not force-close when it is run. The usability test got a learnability value of 100%, an efficiency of 0.0478 goal/sec, and an error of 0 or no error. Testing with the SUS approach to get a satisfaction score obtained 93.4 results with criteria A (90-100). User participation testing resulted in 81% of students doing assignments on time which increased from the previous 53% with a correlation of increasing student learning outcomes obtained from an average score of 68.8 which previously was 62.9.